Analisis Faktor Risiko Kejadian Hipertensi di Wilayah Kota Depok: Analysis of Risk Factors for Hypertension in the Depok City Area - Asri, Intan Puspita; Pitriani Salamah, Nurul; Maryanah Putri, Anna; Putri Nabila E, Shofia; Khairunnisa, Aisyah; Afifah, Faidah; Kusumastuti, Istiana (Journal of Public Health Education, 2022)
Introduction: Hypertension is a non-communicable disease which is often called "the silent killer" because it often occurs without complaint so that sufferers are not aware of it, and then find themselves having a disease or complications from hypertension. Hypertension cases according to WHO 2015 data show that there are around 1.13 billion people in the world and it is estimated that by 2025 there will be 1.5 billion people affected by hypertension and every year 9.4 million people will die from hypertension. Objective: This research was conducted to analyze the risk factors for hypertension in the Depok City area. Methods: This research uses qualitative methods which are carried out online through Google form observations (questionnaires). Data processing was carried out from secondary data (Depok City Health Profile 2019 and other supporting journals) and primary data (questionnaire – Google Form) using Microsoft Excel. Results: The results of this study show that genetic factors, behavioral factors, and health service factors are risk factors for the incidence of hypertension in the Depok City area. The coverage of informants who experienced hypertension was 98 (9.6%) out of 207 (21%) who had a risk of genetic disease. Conclusion: The biggest factors associated with the incidence of hypertension in Depok City were lack of physical activity for 54 people out of 98 hypertension incidents and not having regular health checks for 59 people out of 98 hypertension incidents. To increase physical activity and regular health checks, provide education about good healthy lifestyles so that people want to improve their lifestyles and avoid the risk of hypertension.